2022
DOI: 10.2460/javma.20.10.0559
|View full text |Cite
|
Sign up to set email alerts
|

Presence of bronchial nodules, younger age, and heavier body weight are associated with a diagnosis of eosinophilic lung disease in dogs with cough

Abstract: OBJECTIVE To describe the association between a diagnosis of eosinophilic lung disease (ELD) in dogs with signalment and bronchoscopic features and evaluate the accuracy of visualization of nodules for the diagnosis of ELD. ANIMALS 781 dogs with cough that underwent bronchoscopy between 2014 and 2016. PROCEDURES Data were extracted from the medical records of each included dog. Multivariable logistic regression was performed to investigate associations between ELD and patient characteristics. RESULTS ELD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
13

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 26 publications
0
4
0
13
Order By: Relevance
“…Notably, the CT features are not specific for lungworm infection, and other infectious and inflammatory bronchopneumopathies can also be considered. Recently it was reported that bronchial mucosal nodules can also be seen on bronchoscopy in dogs with eosinophilic lung disease, with a prevalence of 13.1% 12 . Parasites were observed in BAL cytology in 3.8% of the sample population in that study; however, no correlation was found between the presence of bronchial nodules and parasitic infection 12 .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Notably, the CT features are not specific for lungworm infection, and other infectious and inflammatory bronchopneumopathies can also be considered. Recently it was reported that bronchial mucosal nodules can also be seen on bronchoscopy in dogs with eosinophilic lung disease, with a prevalence of 13.1% 12 . Parasites were observed in BAL cytology in 3.8% of the sample population in that study; however, no correlation was found between the presence of bronchial nodules and parasitic infection 12 .…”
Section: Discussionmentioning
confidence: 68%
“…Parasites were observed in BAL cytology in 3.8% of the sample population in that study; however, no correlation was found between the presence of bronchial nodules and parasitic infection 12 . Other reported causes of bronchial nodules or polyps in humans include exposure to inhalation of smoke, toxins, or thermal injury 12 . This further supports the necessity to consider other differentials when the described CT features are noted.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…ELD haben ein breites Spektrum von klinischen Symptomen, radiologischen und endoskopischen Veränderungen [2,3]. Husten stellt das Leitsymptom dar [2][3][4].…”
Section: Introductionunclassified